Lighting does matter: preliminary assessment on office workers - Sivaji, Ashok; Shopian, Sajidah; Mohd Nor, Zulkifle; Chuan, Ngip Khean; Mohd Tamrin, Shamsul Bahri (Elsevier, 2013)
Correlated color temperatures (CCT) of light play an important role in human psychological and physiological needs. This study aims is to find out the effects of warm white (WW), cool white (CW) and artificial daylight (DL) on worker's performances, alertness, visual comfort and preferences. With the use of eye tracker and modified Office Lighting Survey, we have conducted a preliminary controlled experiment with 10 office workers. Result reveals significant increases of alertness levels when using WW lighting. We conclude that CW and DL lights were more beneficial in office setting for computer-based tasks and recommend future comprehensive study undertaken.